2007
DOI: 10.1002/humu.20502
|View full text |Cite
|
Sign up to set email alerts
|

A new variant database for mismatch repair genes associated with Lynch syndrome

Abstract: Mutations in some mismatch repair (MMR) genes are associated with Lynch syndrome (LS; also called hereditary nonpolyposis colorectal cancer [HNPCC]), an autosomal dominant cancer susceptibility syndrome. Colorectal cancer (CRC) is the most frequent cancer observed in LS. However, tumors occur at a variety of extracolonic sites and individuals may have multiple primary cancers. LS is the most common hereditary form of CRC, accounting for approximately 1% of all CRC. Since the first account of mutations in MSH2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
94
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 27 publications
0
94
0
Order By: Relevance
“…Consistent with the central role of MutS␣ in detecting and signaling responses to mismatched and damaged DNA, the loss of MSH2 or MSH6 activity results in accumulation of somatic mutations in tumor cells and resistance to the genotoxic effects of many DNA damaging agents (4,21). Edelmann and co-workers generated two knock-in mouse strains harboring Msh2 G674A or Msh6 T1217D alleles and found that the mice developed cancer, exhibited microsatellite instability, and yielded embryonic fibroblasts that displayed impaired MMR in vitro.…”
Section: The Heterodimeric Human Msh2-msh6 Protein Initiates Dna Mismmentioning
confidence: 84%
“…Consistent with the central role of MutS␣ in detecting and signaling responses to mismatched and damaged DNA, the loss of MSH2 or MSH6 activity results in accumulation of somatic mutations in tumor cells and resistance to the genotoxic effects of many DNA damaging agents (4,21). Edelmann and co-workers generated two knock-in mouse strains harboring Msh2 G674A or Msh6 T1217D alleles and found that the mice developed cancer, exhibited microsatellite instability, and yielded embryonic fibroblasts that displayed impaired MMR in vitro.…”
Section: The Heterodimeric Human Msh2-msh6 Protein Initiates Dna Mismmentioning
confidence: 84%
“…The rest are sporadic cases caused by the hypermethylation of the MLH1 gene promoter 82 . More than 1, 500 germline variants have been found in the MMR genes along with promoter methylation, somatic deletions, or point mutations [85][86][87] . The germline hypermethylations in MLH1 and MSH2 may also increase susceptibility [88][89][90] .…”
Section: Microsatellite Instabilitymentioning
confidence: 99%
“…[17][18][19] Of the cases with loss of MSH2 immunohistochemical staining, approximately twothirds of identifiable mutations in MSH2 are point mutations or small insertions and deletions, whereas the remaining one-third are large gene rearrangements and deletions. 20,21 However, mutations in MSH2 are not identified in up to 20% of the cases expected to have such an alteration.…”
mentioning
confidence: 99%